All the wrong places : a life lost and found - Connors, Philip (W.W. Norton & Company, 2015)
"The prize-winning author of Fire Season returns with the heartrending story of his troubled years of flight. Philip Connors's Fire Season, an account of the decade he spent working in a fire-lookout tower high above the remotest part of New Mexico, won the Banff Mountain Book Grand Prize and the Reading the West Book Award, and Amazon named it the Best Nature Book of the Year. Now Connors returns with the story of what drove him up to the tower in the first place: the wilderness years he spent reeling in the wake of a family tragedy. This is an unforgettable account of grappling with a shattered sense of purpose, from his family's failing pig farm in Minnesota to a crack-addled Brooklyn neighborhood to the mountains of New Mexico, where he puts the pieces of his life back together. Like Cheryl Strayed's Wild, this is a finely wrought look back at wayward youth--and a redemptive story about discovering one's place in the world"--Provided by publisher.